Structure robotic for vertical oil pipeline design methodology. - Urdaneta, María; García, Cecilia; Saltaren, Roque; Contreras, Gustavo; Ejarque, Gonzalo (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper proposes the application of the methodology for deployment of the quality function to de- fine the design criteria of a sliding robot to work in inspection and maintenance in oil wells. This study analyzes the system initially and the options for placement of a robotic structure evaluating alternatives and considering a robotic structure for this purpose. For that purpose a survey by consulting various experts on the topic with the aim of defining the characteristics that have the robot in accordance with the critical requirements in the application. In this paper we show the results obtained by the matrix QFD (Quality Function Deployment) when the input data are provided by the panel respondents. From these results it is possible to determine the technical requirements to be met by the robotic structure that you want to design.